Psychology or Psychological Science?: A Survey of Graduate Psychology Faculty Regarding Program Names. (April 2018) - Collisson, Brian; Rusbasan, David
The question of renaming graduate psychology programs to psychological science is a timely and contentious issue. To better understand why some programs, but not others, are changing names, we surveyed chairpersons (Study 1) and faculty (Study 2) within graduate psychology and psychological science programs. Within psychology programs, a name change was often perceived as unnecessary, nonrepresentative, or intimidating to science-averse students. Within psychological science programs, a name change was often perceived as better conveying the science of psychology to others, a scientific/research focus, or interdisciplinary partnerships. Differences of opinion may be due to psychological science, as compared to psychology, faculty's greater concern about conveying psychological science to others, clarifying their program's focus, and partnering with other sciences.